Pelaksanaan Program Kegiatan KKG PAI SD Kabupaten Banyumas Dalam Peningkatan Kompetensi Guru di Masa Pandemi Covid-19 - Winarni; Muhammad Misbah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2021)
KKG is a forum for gathering and communication between teacher subjects, as well as KKG PAI SD in Banyumas Regency. This activity is a forum for developing teacher competence by providing various forms of activities that are adapted to health protocols during the pandemic. The purpose of this study is to analyze and describe the implementation of PAI SD Teacher Working Group (KKG PAI SD) in improving teacher competence in Banyumas Regency. This research uses descriptive analytical research methods, with data collection tools: observations, interviews, documentation, and triangulation. Based on the results of research and discussion, it can be concluded that; PAI SD KKG Group effectively improves teacher competence in Banyumas Regency based on the implementation of KKG activity programs, types of activity programs, successful activity planning, implementation of activity management, effectiveness of KKG in improving the competence of teachers before and after having held KKG; Obstacles in improving teacher competence, namely the difficulty of making the right strategy to attract teachers to participate in KKG activities, finding interesting, effective and efficient learning methods, determining media relevant to learning materials in the era of covid-19 protesters, low IT mastery and less maximal innovation. The support capacity of qualified and professional school personnel is still lacking, and insufficient existence; and the efforts that have been made by KKG in improving the competence of teachers determine the right strategy to attract teachers to follow the KKG is to bring up a varied program of activities. (KKG merupakan wadah perkumpulan dan komunikasi antar guru mapel, begitu juga KKG PAI SD di Kabupaten Banyumas. Kegiatan ini merupakan wadah pengembangan kompetensi guru dengan memberikan berbagai bentuk kegiatan yang disesuaikan dengan protokol kesehatan pada masa pandemi ini. Tujuan penelitian ini adalah menganalisa dan mendeskripsikan pelaksanaan KKG PAI SD dalam meningkatkan kompetensi guru di Kabupaten Banyumas. Metode yang digunakan deskritif analitik, alat pengumpulan data; observasi, wawancara, dokumentasi. Hasil penelitian menunjukkan; Kelompok KKG PAI SD efektif meningkatkan kompetensi guru di Kabupaten Banyumas berdasarkan pelaksanaan program kegiatan KKG, jenis program kegiatan, keberhasilan perencanaan kegiatan, pelaksanaan pengelolaan kegiatan, efektivitas KKG dalam meningkatkan kompetensi guru sebelum dan setelah diadakan KKG; Hambatan dalam meningkatkan kompetensi guru yaitu sulitnya membuat strategi yang tepat untuk menarik minat guru mengikuti kegiatan KKG, menemukan metode pembelajaran yang menarik, efektif dan efesien, menentukan media yang relevan dengan materi pembelajaran di masa pendemi covid-19, penguasaan IT yang masih rendah dan inovasi yang kurang maksimal. Daya dukung personil sekolah berkualitas dan profesional masih kurang, dan belum mencukupi keberadaannya; dan Upaya-upaya yang telah dilakukan pengurus KKG PAI SD dalam meningkatkan kompetensi guru yaitu dengan memunculkan program kegiatan yang variatif, sehingga guru yang mengikuti kegiatan KKG memiliki pengetahuan yang lebih baik di banding sebelumnya.)